A European Res publica - Ola Zetterquist (Oñati Socio-Legal Series)
The article analyses the fundamental constitutional enigma of the European Union (EU), namely whether the EU can be considered as a (from its Member States) separate and independent constitutional legal order. The EU is often referred to as a legal order sui generis, i.e. of a unique character that defies traditional definitions. More specifically, the notion of an independent and separate EU is at odds with the idea of the sovereign state. The notion of the EU as a legal order sui generis is too much influenced by the models of the sovereign state and sovereignty (in the vein of Thomas Hobbes). The key component in the Hobbesian idea of sovereignty is freedom as non-interference. A sovereign state is consequently a state that is free from, i.e. not interfered with by, external actors like, for example, the EU. Put differently, either the EU is sovereign or the Member States are sovereign.